IslamGRID: Knowledge Management at Jakim - Abdul Wahid, Al- Abrar; Idriss, Hissein Aboubakar; Rameez, Mamdhooh; AlMohaifer, Mohammad Salem; Ahmad Dahlan, Abdul Rahman; Dolmoin, Kamarudin (2010)
IslamGRID was developed to collect, preserve, disseminate and promote knowledge of Islam to all Muslims globally, whether in the administrative, industrial and commercial. With the advent of Information Technology and the increase of the amount of information that organizations have to deal with, there is a requirement to put strategic process in place to ensure the effective management of knowledge. This case study research looks into 3 main areas of a Knowledge Management (KM) System (KMS) (i. People; ii. Process; and iii. Technology) and their relationship, which might affect the effectiveness of the IslamGRID to the Islamic community (Ummah). The application of these areas would be for JAKIM, JAIN, Muslims as well as non-Muslims.